Effects of the COVID-19 pandemic on the pediatric emergency department: a single institution experience - Isabella V. Masler; Nipam Shah; Shea A. Duerring; Kathy R. Monroe (BMC, 2022)
Abstract Background The COVID-19 pandemic resulted in drastic decreases in volume for most pediatric emergency departments (ED). Injuries have persisted and there is concern that injuries may have increased during the pandemic. This study evaluates the impact of the COVID-19 pandemic on ED patient trends at a freestanding children's hospital. Results Despite an average annual increase of 1100 patients per year between 2017 and 2019, this ED saw a decrease of over 25,000 patients in 2020. The number of trauma alerts increased from 341 in 2017 to 571 in 2020 and those numbers remained stable (568-571) in 2020 compared to 2019. The percent of total volume accounted for by trauma alerts increased from 0.65 to 1.2% between 2019 and 2020 (following the trend of 0.48% in 2017 to 0.56% in 2018). Historically, motor vehicle crashes account for the majority of the trauma alerts, though the number of trauma alerts from firearm-related injuries increased from 36 per year in 2018 to 44 in 2019 to 66 (12% of total trauma alerts) in 2020. Conclusions While total volumes of patients being seen decreased, the number of trauma alerts remained stable resulting in an increased percentage of trauma alert patients. This indicates that severe injuries requiring trauma alert activation did not diminish during the pandemic. These trends have implications for prevention as well as implications for ED staffing. Changing trends in types of severe injuries are noted.